A composite aluminum material with thermal conductivity and preparation method thereof
By adding thermal conductivity and reinforcement phases to the aluminum alloy, an iron plating layer and a tungsten metal carbide layer are formed, and combined with hexagonal boron nitride and carbon nanotubes, the problem of insufficient thermal conductivity and mechanical strength of the aluminum alloy is solved, and efficient heat dissipation and High-strength composite aluminum material.
Patent Information
- Application Number
- CN202410573579.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-10
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-05-10
AI Technical Summary
Aluminum alloy materials have shortcomings in high strength and thermal conductivity, which are difficult to meet the heat dissipation needs of aerospace and electronic devices.
Using composite aluminum materials including iron, silicon, manganese, magnesium, thermal conductivity and reinforcement phases, iron plating and tungsten metal carbide layer are formed through electroless plating and electroplating, combining hexagonal boron nitride and carbon nanotubes to enhance the thermal conductivity of aluminum alloys. and mechanical properties.
It significantly improves the thermal conductivity and mechanical properties of composite aluminum, meets the needs of efficient heat dissipation and high-strength applications, and forms a stable thermal conductivity network and a solid combination.
Smart Images

Figure BDA0004831685290000111
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal materials, and in particular to a composite aluminum material with thermal conductivity and a preparation method thereof. Background Art
[0002] Aluminum alloy is a metal material with low density, light weight, but high strength and hardness. Aluminum alloy also has strong plasticity and machinability. These unique properties enable it to meet the needs of various industries. For example, in the aerospace and automobile manufacturing fields, aluminum alloy can manufacture lightweight components and improve the comprehensive performance of aircraft or automobiles. At the same time, aluminum alloy also has excellent corrosion resistance, so it has broad application prospects in construction, marine engineering, chemical equipment and other fields.
[0003] However, despite the many advantages of aluminum alloys, there are also some challenges and limitations. First, the strength of aluminum alloys is relatively low, which limits its use in certain high-strength application scenarios. Secondly, although the thermal conductivity of aluminum alloys is relatively high, it is still insufficient compared to the needs of certain specific industries. For example, in the aerospace field, high-temperature components of aircraft need to withstand extremely high temperatures and dissipate heat quickly, and the thermal conductivity of aluminum alloys is difficult to meet this demand. In addition, in the field of heat dissipation of electronic devices, with the increase in integration, the heat dissipation problem has become more serious, and the thermal conductivity of aluminum alloys cannot fully meet the requirements of efficient heat dissipation.
[0004] In order to overcome these shortcomings, researchers are working on developing new aluminum alloy materials and improving processing technology. Through alloying, heat treatment and preparation of composite materials, the strength and hardness of aluminum alloys can be improved and their application areas can be expanded. For example, the invention patent with publication number CN108866397B discloses a method for preparing heat-resistant aluminum alloy materials and a high thermal conductivity aluminum alloy. By strictly controlling the proportion of each raw material and utilizing the synergy between the components, the prepared aluminum alloy material has a higher thermal conductivity and better die-casting mechanical properties. Therefore, the comprehensive performance of the aluminum alloy can be enhanced by adjusting the raw materials in the formula. Summary of the invention
[0005] The purpose of the present invention is to provide a composite aluminum material with thermal conductivity and a preparation method thereof, which solves the problem of insufficient thermal conductivity and mechanical strength of aluminum alloy materials.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A composite aluminum material with thermal conductivity is made of raw materials including the following mass percentages: 0.15-0.25% iron, 1.0-2.0% silicon, 0.5-1.5% manganese, 3.0-5.0% magnesium, 1.0-3.0% thermal conductive phase, 2.0-3.5% reinforcing phase, and the balance is aluminum and inevitable impurities;
[0008] The preparation method comprises the following steps:
[0009] The first step is to weigh each raw material according to the mass percentage for later use;
[0010] Step 2: Raise the furnace temperature to 760-770°C, add iron, silicon, manganese, magnesium and aluminum into the furnace, and after they are completely melted, remove slag and degassing, let them stand for 20-30 minutes to form alloy liquid 1;
[0011] Step 3: Under nitrogen protection, add the heat conductive phase and the reinforcing phase into the alloy liquid, stir and mix evenly to form alloy liquid II;
[0012] The fourth step is to degas the alloy liquid 2, filter and remove the scum, adjust the temperature to 680-700°C, pour it into a casting mold, and after cooling, a composite aluminum material can be formed.
[0013] A composite aluminum material with thermal conductivity is prepared by adopting the preparation method.
[0014] As a further solution of the present invention, in the second step, during the slag removal treatment, the temperature is adjusted to 720-730°C, and 1.5-2‰ of a refining agent is added, and the refining is performed for 3-5 minutes.
[0015] As a further solution of the present invention, in the third step, the method for preparing the thermally conductive phase comprises the following steps:
[0016] Step 1: Add ferrous sulfate, disodium ethylenediaminetetraacetate, sodium potassium tartrate, sodium hydroxide, 2,2'-bipyridine and sodium hypophosphite into purified water, stir mechanically to mix, and prepare a chemical plating solution;
[0017] Step 2, adding hexagonal boron nitride to the chemical plating solution, stirring and dispersing it evenly at a rate of 3000-4000 r / min, controlling the temperature to 50-60°C, stirring at a stirring rate of 1000-1500 r / min for 20-40 minutes, taking it out, washing it and drying it to form a boron nitride plating material;
[0018] Step 3: Add boron nitride plating material to the plating solution and adjust the current density to 15-25mA / cm 2 , take it out after electroplating for 20-30 minutes, wash it, and vacuum dry it to obtain the thermal conductive phase.
[0019] Specifically, in step one, the raw materials are mixed and configured to form a chemical plating solution, and first, chemical iron plating is performed on the surface of hexagonal boron nitride. Studies have found that although this chemical iron plating method can form a uniform coating on the surface of hexagonal boron nitride, this coating is relatively thin and is prone to falling off during the subsequent production of aluminum alloys. Although the electroplating method can form a thicker coating, due to the shielding effect, the coating will be very uneven, and it is difficult to form a complete coating on the surface of hexagonal boron nitride. Therefore, after a large number of experiments, the method of first chemical plating and then electroplating is adopted to deposit a uniform and thick iron coating on the surface of hexagonal boron nitride to obtain a thermal conductive phase.
[0020] As a further embodiment of the present invention, in step 1, the concentration of ferrous sulfate is 15-20 g / L, the concentration of disodium ethylenediaminetetraacetate is 20-30 g / L, the concentration of potassium sodium tartrate is 10-20 g / L, the concentration of sodium hydroxide is 14-16 g / L, the concentration of 2,2'-bipyridine is 3-6 mg / L, and the concentration of sodium hypophosphite is 5-10 mg / L.
[0021] As a further solution of the present invention, in step 3, the preparation method of the electroplating solution is as follows:
[0022] Step S1, mixing ferrous sulfate with purified water to prepare a ferrous sulfate solution with a concentration of 180-200 g / L; then mixing potassium nitrate with purified water to prepare a potassium nitrate solution with a concentration of 5-15 g / L;
[0023] Step S2, mixing the ferrous sulfate solution and the potassium nitrate solution in a volume ratio of 1:1, and then adding sulfuric acid with a concentration of 40-50 g / L and hydrochloric acid with a concentration of 50-60 mg / L to the formed mixed solution, stirring and mixing, to form an electroplating solution.
[0024] As a further solution of the present invention, in the third step, the preparation method of the reinforcing phase is as follows:
[0025] Place carbon nanotubes in the reaction chamber of a chemical vapor deposition device, place tungsten hexacarbonyl in a sublimation device, pass nitrogen, exhaust the air in the device, control the temperature in the sublimation device to 120-130°C, then pass a mixture of nitrogen and carbon monoxide into the tungsten hexacarbonyl sublimation device, wherein the flow rate of nitrogen is 140-160mL / min, and the flow rate of carbon monoxide is 30-50mL / min. After 10-20 minutes, close the device, take out the material in the reaction chamber, and the enhanced phase can be obtained.
[0026] Specifically, a tungsten metal carbide layer is chemically deposited on the surface of the carbon nanotube using chemical vapor deposition. Tungsten hexacarbonyl sublimes under high temperature conditions. As the mixed gas is introduced, the sublimated tungsten hexacarbonyl is brought into the reaction chamber by the mixed gas. Then, a multi-step deposition reaction occurs on the surface of the carbon nanotube in the reaction chamber, eventually forming a carbon nanotube coated with a tungsten metal carbide layer.
[0027] As a further solution of the present invention, in the fourth step, the degassing treatment is carried out at a temperature of 710-720° C. under nitrogen protection.
[0028] Beneficial effects of the present invention:
[0029] (1) The present invention uses hexagonal boron nitride with iron plating on the surface as a thermal conductive phase to add and modify the aluminum alloy material. The iron plating layer formed by chemical plating and electroplating can form a micro three-dimensional structure on the surface of the hexagonal boron nitride. Then, through the good interface wettability between the iron layer and the aluminum alloy, it is firmly embedded in the aluminum alloy matrix, effectively solving the interface wettability problem between the inorganic non-metallic material hexagonal boron nitride and the metal material, avoiding the problem of reduced strength of the alloy material due to interface problems between them, and can also utilize the excellent thermal conductivity of hexagonal boron nitride, combined with the excellent thermal conductivity of the aluminum alloy itself, so that the prepared composite aluminum material exhibits excellent thermal conductivity.
[0030] (2) The present invention electroplates a tungsten metal carbide layer on the surface of the carbon nanotubes, and utilizes the tungsten metal carbide layer to produce a "transition" layer between the aluminum alloy metal phase and the carbon nanotube non-metal phase. The metal tungsten can enter the aluminum lattice, causing the aluminum lattice to be distorted. This will hinder the relative movement of aluminum atoms, thereby forming a high-strength bonding force in the "transition" zone, forming a strong bond between them. Then, the carbon nanotubes themselves are utilized to form a dispersed distribution in the aluminum alloy matrix, thereby preventing grain boundary slip and dislocation movement in the form of obstacles, thereby effectively enhancing the mechanical properties of the aluminum alloy matrix.
[0031] (3) The present invention adjusts the formula and utilizes the alloy phase and bonding phase formed between the various components in the formula to effectively enhance the mechanical properties and thermal conductivity of the composite aluminum material. In particular, the hexagonal boron nitride in the thermal conductive phase and the reinforcing phase can be dispersed with the carbon nanotubes in the reinforcing phase in the aluminum alloy matrix to form a stable thermal conductive network, thereby further enabling the composite aluminum material to exhibit excellent thermal conductivity.
[0032] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. DETAILED DESCRIPTION
[0033] The technical solution of the present invention will be clearly and completely described below in conjunction with this embodiment. Obviously, the described embodiment is only a part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] The heat conducting phases in the following examples and comparative examples were prepared by the following method:
[0035] Step 1, add ferrous sulfate, disodium ethylenediaminetetraacetate, potassium sodium tartrate, sodium hydroxide, 2,2'-bipyridine and sodium hypophosphite to purified water, so that the concentration of ferrous sulfate is 20g / L, the concentration of disodium ethylenediaminetetraacetate is 25g / L, the concentration of potassium sodium tartrate is 15g / L, the concentration of sodium hydroxide is 15g / L, the concentration of 2,2'-bipyridine is 5mg / L, and the concentration of sodium hypophosphite is 10mg / L, and mix by mechanical stirring to prepare a chemical plating solution;
[0036] Step 2: Add 5 g of hexagonal boron nitride to 200 mL of chemical plating solution, stir and disperse evenly at a rate of 4000 r / min, control the temperature to 55°C, stir at a stirring rate of 1000 r / min for 30 min, take out, wash and dry to form a boron nitride plating material;
[0037] Step 3: Add boron nitride plating material to the plating solution and adjust the current density to 20mA / cm 2 , take it out after electroplating for 30 minutes, wash it, and vacuum dry it to obtain the thermal conductive phase.
[0038] The preparation method of the electroplating solution is as follows:
[0039] Step S1, mixing ferrous sulfate with purified water to prepare a ferrous sulfate solution with a concentration of 200 g / L; then mixing potassium nitrate with purified water to prepare a potassium nitrate solution with a concentration of 10 g / L;
[0040] Step S2, mixing 100 mL of ferrous sulfate solution with 100 mL of potassium nitrate solution, and then adding 10 mL of 40 g / L sulfuric acid and 50 mg / L hydrochloric acid to the formed mixed solution, stirring and mixing, to form an electroplating solution.
[0041] The reinforcing phases in the following examples and comparative examples were prepared by the following method:
[0042] Place carbon nanotubes in the reaction chamber of a chemical vapor deposition device, place hexacarbonyl tungsten in a sublimation device, pass nitrogen, exhaust the air in the device, control the temperature in the sublimation device to 120°C, then pass a mixture of nitrogen and carbon monoxide into the hexacarbonyl tungsten sublimation device, wherein the flow rate of nitrogen is 150 mL / min, and the flow rate of carbon monoxide is 40 mL / min. After 15 minutes, close the device, take out the material in the reaction chamber, and the enhanced phase can be obtained.
[0043] Example 1
[0044] A composite aluminum material with thermal conductivity is made of raw materials including the following mass percentages: 0.15% iron, 1.0% silicon, 0.5% manganese, 3.0% magnesium, 1.0% thermal conductive phase, 2.0% reinforcing phase, and the balance is aluminum and inevitable impurities;
[0045] The preparation method of the composite aluminum material comprises the following steps:
[0046] The first step is to weigh each raw material according to the mass percentage for later use;
[0047] Step 2: Raise the furnace temperature to 760°C, add iron, silicon, manganese, magnesium and aluminum into the furnace, and after they are completely melted, adjust the temperature to 720°C, add 1.5‰ of Mg-based refining agent, refine for 3 minutes, and then degasify and stand for 20 minutes to form alloy liquid 1;
[0048] Step 3: Under nitrogen protection, add the heat conductive phase and the reinforcing phase into the alloy liquid, stir and mix evenly to form alloy liquid II;
[0049] The fourth step is to degas the alloy liquid 2, remove the scum by filtering, adjust the temperature to 680°C, pour it into a casting mold, and after cooling, a composite aluminum material can be formed.
[0050] Example 2
[0051] A composite aluminum material with thermal conductivity is made of raw materials including the following mass percentages: 0.2% iron, 1.5% silicon, 1.0% manganese, 4.0% magnesium, 2.0% thermal conductive phase, 2.5% reinforcing phase, and the balance is aluminum and inevitable impurities;
[0052] The preparation method of the composite aluminum material comprises the following steps:
[0053] The first step is to weigh each raw material according to the mass percentage for later use;
[0054] Step 2: Raise the furnace temperature to 770°C, add iron, silicon, manganese, magnesium and aluminum into the furnace, and after they are completely melted, adjust the temperature to 730°C, add 2‰ of Mg-based refining agent, refine for 4 minutes, and then degasify and stand for 25 minutes to form alloy liquid 1;
[0055] Step 3: Under nitrogen protection, add the heat conductive phase and the reinforcing phase into the alloy liquid, stir and mix evenly to form alloy liquid II;
[0056] The fourth step is to degas the alloy liquid 2, remove the scum by filtering, adjust the temperature to 690°C, pour it into a casting mold, and form a composite aluminum material after cooling.
[0057] Example 3
[0058] A composite aluminum material with thermal conductivity is made of raw materials including the following mass percentages: 0.2% iron, 1.8% silicon, 1.2% manganese, 4.5% magnesium, 2.5% thermal conductive phase, 3.0% reinforcing phase, and the balance is aluminum and inevitable impurities;
[0059] The preparation method of the composite aluminum material comprises the following steps:
[0060] The first step is to weigh each raw material according to the mass percentage for later use;
[0061] Step 2: Raise the furnace temperature to 770°C, add iron, silicon, manganese, magnesium and aluminum into the furnace, and after they are completely melted, adjust the temperature to 730°C, add 2‰ Mg-based refining agent, refine for 5 minutes, and then degasify and stand for 30 minutes to form alloy liquid 1;
[0062] Step 3: Under nitrogen protection, add the heat conductive phase and the reinforcing phase into the alloy liquid, stir and mix evenly to form alloy liquid II;
[0063] The fourth step is to degas the alloy liquid 2, remove the scum by filtering, adjust the temperature to 700°C, pour it into a casting mold, and after cooling, a composite aluminum material can be formed.
[0064] Example 4
[0065] A composite aluminum material with thermal conductivity is made of raw materials including the following mass percentages: 0.25% iron, 2.0% silicon, 1.5% manganese, 5.0% magnesium, 3.0% thermal conductive phase, 3.5% reinforcing phase, and the balance is aluminum and inevitable impurities;
[0066] The preparation method of the composite aluminum material comprises the following steps:
[0067] The first step is to weigh each raw material according to the mass percentage for later use;
[0068] Step 2: Raise the furnace temperature to 770°C, add iron, silicon, manganese, magnesium and aluminum into the furnace, and after they are completely melted, adjust the temperature to 730°C, add 2‰ Mg-based refining agent, refine for 5 minutes, and then degasify and stand for 30 minutes to form alloy liquid 1;
[0069] Step 3: Under nitrogen protection, add the heat conductive phase and the reinforcing phase into the alloy liquid, stir and mix evenly to form alloy liquid II;
[0070] The fourth step is to degas the alloy liquid 2, remove the scum by filtering, adjust the temperature to 700°C, pour it into a casting mold, and after cooling, a composite aluminum material can be formed.
[0071] Comparative Example 1
[0072] A composite aluminum material, which is different from Example 3 in that the heat conduction phase is removed, and the rest is the same as Example 3.
[0073] Comparative Example 2
[0074] A composite aluminum material, which is different from Example 3 in that the reinforcing phase is replaced with carbon nanotubes, and the rest is the same as Example 3.
[0075] Comparative Example 3
[0076] A composite aluminum material, which is different from Example 3 in that the reinforcement phase is removed, and the rest is the same as Example 3.
[0077] Test Case
[0078] The mechanical properties and thermal conductivity of the composite aluminum materials in Examples 1 to 3 and Comparative Examples 1 to 3 were tested, and the results are recorded in Table 1:
[0079] Table 1 - Performance test results
[0080]
[0081] Analysis of the test results in Table 1 shows that the composite aluminum material with the addition of the reinforcing phase and the thermal conductive phase obviously has good mechanical properties and thermal conductivity at the same time, which can meet the needs of industry use. After removing the thermal conductive phase, the thermal conductivity of the composite aluminum material is significantly reduced. When the reinforcing phase is replaced with carbon nanotubes without surface coating, the mechanical properties are significantly reduced due to the interface wetting problem between them. After removing the reinforcing phase, the mechanical properties are further reduced.
[0082] Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core ideas, including the best mode, and also enable any technician in the field to practice the present invention, including making and using any device or system, and implementing any combined method. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, the present invention can also be improved and modified, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements similar to the literal expression of the claims, or if they include equivalent structural elements that are not substantially different from the literal expression of the claims, then these other embodiments should also be included in the scope of the claims.
[0083] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a composite aluminum material with thermal conductivity, characterized in that: The composite aluminum material comprises the following raw materials in percentage by mass: 0.15-0.25% iron, 1.0-2.0% silicon, 0.5-1.5% manganese, 3.0-5.0% magnesium, 1.0-3.0% heat conductive phase, 2.0-3.5% reinforcing phase, and the balance is aluminum and unavoidable impurities; The preparation method comprises the following steps: The first step is to weigh each raw material according to the mass percentage for later use; Step 2: Raise the furnace temperature to 760-770°C, add iron, silicon, manganese, magnesium and aluminum into the furnace, and after they are completely melted, remove slag and degassing, let them stand for 20-30 minutes to form alloy liquid 1; Step 3: Under nitrogen protection, add the heat conductive phase and the reinforcing phase into the alloy liquid, stir and mix evenly to form alloy liquid II; The preparation method of the thermally conductive phase comprises the following steps: Step 1: Add ferrous sulfate, disodium ethylenediaminetetraacetate, sodium potassium tartrate, sodium hydroxide, 2,2'-bipyridine and sodium hypophosphite into purified water, stir mechanically to mix, and prepare a chemical plating solution; Step 2, adding hexagonal boron nitride to the chemical plating solution, stirring and dispersing it evenly at a rate of 3000-4000 r / min, controlling the temperature to 50-60°C, stirring at a stirring rate of 1000-1500 r / min for 20-40 minutes, taking it out, washing it and drying it to form a boron nitride plating material; Step 3: Add boron nitride plating material to the plating solution and adjust the current density to 15-25mA / cm 2 , take it out after electroplating for 20-30 minutes, wash it, and vacuum dry it to obtain the thermal conductive phase; The fourth step is to degas the alloy liquid 2, filter and remove the scum, adjust the temperature to 680-700°C, pour it into a casting mold, and after cooling, a composite aluminum material can be formed.
2. The method for preparing a composite aluminum material with thermal conductivity according to claim 1, characterized in that: In the second step, during the slag removal treatment, the temperature is adjusted to 720-730°C, and 1.5-2‰ of refining agent is added, and the refining is carried out for 3-5 minutes.
3. The method for preparing a composite aluminum material with thermal conductivity according to claim 1, characterized in that: In step 1, the concentration of ferrous sulfate is 15-20 g / L, the concentration of disodium ethylenediaminetetraacetate is 20-30 g / L, the concentration of potassium sodium tartrate is 10-20 g / L, the concentration of sodium hydroxide is 14-16 g / L, the concentration of 2,2'-bipyridine is 3-6 mg / L, and the concentration of sodium hypophosphite is 5-10 mg / L.
4. The method for preparing a composite aluminum material with thermal conductivity according to claim 1, characterized in that: In step 3, the preparation method of the electroplating solution is as follows: Step S1, mixing ferrous sulfate with purified water to prepare a ferrous sulfate solution with a concentration of 180-200 g / L; then mixing potassium nitrate with purified water to prepare a potassium nitrate solution with a concentration of 5-15 g / L; Step S2, mixing the ferrous sulfate solution and the potassium nitrate solution in a volume ratio of 1:1, and then adding sulfuric acid with a concentration of 40-50 g / L and hydrochloric acid with a concentration of 50-60 mg / L to the formed mixed solution, stirring and mixing, to form an electroplating solution.
5. The method for preparing a composite aluminum material with thermal conductivity according to claim 1, characterized in that: In the third step, the preparation method of the reinforcement phase is as follows: Place carbon nanotubes in the reaction chamber of a chemical vapor deposition device, place tungsten hexacarbonyl in a sublimation device, pass nitrogen, exhaust the air in the device, control the temperature in the sublimation device to 120-130°C, then pass a mixture of nitrogen and carbon monoxide into the tungsten hexacarbonyl sublimation device, wherein the flow rate of nitrogen is 140-160mL / min, and the flow rate of carbon monoxide is 30-50mL / min. After 10-20 minutes, close the device, take out the material in the reaction chamber, and the enhanced phase can be obtained.
6. The method for preparing a composite aluminum material with thermal conductivity according to claim 1, characterized in that: In the fourth step, the degassing treatment is carried out at a temperature of 710-720° C. under nitrogen protection.
7. A composite aluminum material with thermal conductivity, characterized in that: The method is prepared according to claim 1.
Citation Information
Patent Citations
Preparation method of high thermal conductivity aluminum alloy materials and high thermal conductivity aluminum alloy
CN108866397B
Silicon particle and carbon nanotube mixing enhanced aluminum-based composite material and preparation method thereof
CN104561847A
High-thermal-conductivity aluminum alloy
CN105483453A
Aluminum-magnesium alloy material for high-toughness structural component and preparation method thereof
CN114015916A